Swallowing Disorder and Inhibition of Cough Reflex Induced by Atropine Sulfate in Conscious Dogs - Tadashi Tsubouchi; Shinji Tsujimoto; Shinichi Sugimoto; Yasunori Katsura; Terumasa Mino; Takaki Seki (Elsevier, 2008)
In this study, the effects of atropine sulfate (atropine) on swallowing and cough reflex were evaluated in the two experimental models in conscious dogs. To evaluate the effects of atropine on swallowing, 1 mL of marker (contrast medium) was injected into the pharynx under X-ray exposure to induce swallowing. Baclofen, used as a positive control, caused marker congestion in the upper esophagus. In our experimental model, atropine (0.02 and 0.1 mg /kg, i.v.) dose-dependently increased not only the number of marker congestions but also that of the swallows. In addition, atropine significantly shortened the onset of first swallowing. In the evaluation of atropine effects on electrically evoked cough reflex induced by two electrodes implanted into the trachea, atropine strongly inhibited the number of coughs at 0.01 or 0.05 mg/kg accompanied with 0.01 or 0.05 mg/kg per hour (i.v.), respectively. These findings indicate that atropine has the potential of causing aspiration pneumonia through induction of swallowing disorder and inhibition of the cough reflex. Keywords:: swallowing disorder, inhibition of cough reflex, anti-cholinergic agent, dog, aspiration pneumonia